2013
DOI: 10.1364/oe.21.018125
|View full text |Cite
|
Sign up to set email alerts
|

Sparse ACEKF for phase reconstruction

Abstract: Abstract:We propose a novel low-complexity recursive filter to efficiently recover quantitative phase from a series of noisy intensity images taken through focus. We first transform the wave propagation equation and nonlinear observation model (intensity measurement) into a complex augmented state space model. From the state space model, we derive a sparse augmented complex extended Kalman filter (ACEKF) to infer the complex optical field (amplitude and phase), and find that it converges under mild conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Methods that use a series of through-focus intensity images (e.g., [3][4][5][6][7][8][9]) are especially popular due to their experimental simplicity. In-focus intensity images contain no phase information; however, defocus introduces phase contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Methods that use a series of through-focus intensity images (e.g., [3][4][5][6][7][8][9]) are especially popular due to their experimental simplicity. In-focus intensity images contain no phase information; however, defocus introduces phase contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this means that one must store and manipulate a 4D covariance matrix of size N 2 (where N is the total number of pixels), so memory requirements are prohibitive. We recently solved this problem by proving that the covariance matrix should be sparse [17], reducing both memory and computational complexity by many orders of magnitude. Note that the sparsity of the covariance matrix does not imply sparsity of the object [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to have efficient minimization of LFA, a large number of planes have to be captured. In a recent publication [8], it was shown that the exponential separa-* E-mail: j.martinez@mchtr.pw.edu.pl tion strategy [8] can mitigate the LFAs on TIE methods by using only a few captured intensities [9].…”
mentioning
confidence: 99%
“…where I 0 is the on-focus intensity, φ is the phase and ∂ z I is the intensity axial derivative that can be estimated using different methods [7,9]. Equation (1) …”
mentioning
confidence: 99%
See 1 more Smart Citation